2004
DOI: 10.1002/cncr.11910
|View full text |Cite
|
Sign up to set email alerts
|

Randomized multicenter Phase II trial of two different schedules of irinotecan combined with capecitabine as first‐line treatment in metastatic colorectal carcinoma

Abstract: BACKGROUND The aim of the current randomized Phase II study was to investigate the efficacy and safety of capecitabine combined with irinotecan as first‐line treatment in metastatic colorectal carcinoma (CRC). METHODS A total of 140 patients received capecitabine at a dose of 1250 mg/m2 twice daily on Days 2–15 and irinotecan at a dose of either 300 mg/m2 on Day 1 (Arm A) or 150 mg/m2 on Days 1 and 8 (Arm B) every 3 weeks. During the course of the study, enrollment was continued using lower doses of capecitabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
79
2
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 38 publications
9
79
2
5
Order By: Relevance
“…Published phase II studies of the irinotecan/capecitabine combination in colorectal cancer have reported similar frequencies and types of grade X3 toxicity, with diarrhoea being the commonest, occurring in around 20% of patients and grade X3 neutropenia, lethargy, nausea and anorexia in around 10 -20% (Bajetta et al, 2004;Borner et al, 2005). Recently, the EORTC 40015 phase III study, comparing 2-weekly irinotecan/LV5FU2 vs 3-weekly irinotecan/capecitabine (both arms7celecoxib) in advanced colorectal cancer, was stopped prematurely because of excessive toxicity (Kohne et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Published phase II studies of the irinotecan/capecitabine combination in colorectal cancer have reported similar frequencies and types of grade X3 toxicity, with diarrhoea being the commonest, occurring in around 20% of patients and grade X3 neutropenia, lethargy, nausea and anorexia in around 10 -20% (Bajetta et al, 2004;Borner et al, 2005). Recently, the EORTC 40015 phase III study, comparing 2-weekly irinotecan/LV5FU2 vs 3-weekly irinotecan/capecitabine (both arms7celecoxib) in advanced colorectal cancer, was stopped prematurely because of excessive toxicity (Kohne et al, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Recently, in a randomised multicentre phase II trial (Bajetta et al, 2004) comparing two different schedules of irinotecan combined with capecitabine as the first-line treatment for metastatic colorectal cancer, diarrhoea, which occurred in 37.8% of the patients at a grade 3/4 intensity, was the main adverse effect of the arm B regimen (capecitabine 1000 mg m À2 twice daily on days 2 -15 and irinotecan 120 mg m À2 on days 1 and 8, every 21 days). However, in the present study, a reduced dose of irinotecan (100 mg m À2 on days 1 and 8) was administered to alleviate adverse effects, and grade 3/4 diarrhoea and neutropenia was only observed in 15 and 10% of the patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have shown the efficacy and safety of capecitabine and irinotecan for advanced colorectal cancer (Tewes et al, 2003;Bajetta et al, 2004;Borner et al, 2005;Kim et al, 2005;Rea et al, 2005), no results have yet been reported for advanced gastric cancer. Accordingly, the current phase II study was conducted to evaluate the efficacy and safety of a combination regimen of capecitabine plus irinotecan in patients with advanced gastric cancer.…”
mentioning
confidence: 99%
“…Phase I/II studies of capecitabine combination with irinotecan (XELIRI) showed comparable response rates compared with 5-FULV-irinotecan combination (Bajetta et al, 2004;Borner et al, 2005;Rea et al, 2005). On the other hand, XELIRI has been related with response rates of 38-45% and a time-to-progression of about of 8 months with manageable side-effect profiles (Tewes et al, 2003;Bajetta et al, 2004;Cartwright et al, 2005).…”
Section: Introductionmentioning
confidence: 99%